PEMBERIAN MAKANAN TAMBAHAN (PMT) PADA IBU HAMIL TRIMESTER III SEBAGAI UPAYA MENGURANGI VOLUME DARAH YANG HILANG SELAMA PERSALINAN DI KOTA YOGYAKARTA - , LASTDES CRISTIANY FRIDAY SIHOMBING, Dr. rer. nat. dr. BJ. Istiti Kandarina ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Prevalence of anemia in Yogyakarta was 25.9% in 2011 and 24.33% in 2012. Anemia may increase blood loss during delivery. Iron supplementation and supplementary feeding can treat anemia. Supplementary feeding program for pregnant women is designed to combat anemia, thus to prevent massive blood loss during delivery. Objectives: To examine the effect of supplementary feeding in pregnant women on blood loss during delivery. Method: This is a quasi-experimental, non-equivalent control treatment groupâs study. Eighty-eight subjects were divided: 42 in the treatment group and 46 in the control group. Treatment group was provided with supplementary food daily for 30 days. Control group was monitored daily consumption of iron tablets for 30 days. Under pad was used to collect lost blood during parturition by. Data were analyzed with STATA program. Results: Treatment group lost less blood during delivery than control group, with mean difference= 47.2 mL and statistically significant with p value =0.008, (95%CI: (-81.7)-(-12.7)). In multiple linear regression models, supplementary feeding adjusted by upper arm circumference can decrease blood loss during delivery, with coefficient of regression = 48.5 ml and statistically significant with p value =0.003 (R2= 0.23, 95%CI: 16.9-80.1). Conclusion: Supplementary feeding in pregnant women resulted in significant decrease in blood loss during delivery